The Integrasi Teknologi dalam Media Pembelajaran PAI Berbasis Deep Learning untuk Mewujudkan Pembelajaran Bermakna di Ponpes Darul Hijrah Putri Martapura - Hanifah, Cahaya (FTIK UIN Sultan Aji Muhammad Idris Samarinda, 2025)
The rapid advancement of information technology has had a significant impact on the world of education, including Islamic education in Islamic boarding schools (pesantren). This study aims to analyze the implementation of deep learning-based technology integration in Islamic Religious Education (PAI) at the Darul Hijrah Puteri Martapura Islamic Boarding School. The activities studied include the use of artificial intelligence (AI) in learning, the implementation of In-House Training (IHT) for teachers, boarding school lectures, mentoring in the development of Deep Learning Plans (RPM), computer-based learning in several subjects, and the examination of the RPMs. The research method used a descriptive qualitative approach using observation, interviews, and documentation studies. The results show that this technology integration creates a learning system that is enjoyable, meaningful, and conscious. AI and deep learning-based training help teachers and students develop critical, reflective, and spiritual thinking skills without abandoning the values ​​of the Islamic boarding school.